Genomic Variation in Dengue Virus Non-Structural Protein 1 (NS1): Genomic Variation in Dengue Virus Non-Structural Protein 1 (NS1) - Saira Mushtaq,; Muhammad Tahir Khan,; Sikandar Hayyat,; Hasnain Javed,; Malik Ihsan Ullah Khan,; Sajjad Ghani, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
To understand in an improved way how the dengue virus (DENV) spreads, presents, and becomes hazardous, researching its genetic makeup is necessary. The positive sense RNA of DENV encodes three structural proteins and seven non-structural proteins. One of the non-structural proteins that aids in the replication of viral RNA is the non-structural protein 1 (NS1). The objective was to identify the most frequently repeated mutations in the NS1 protein in DENV RNA isolated from dengue patients in the province Punjab, Pakistan. Selection of 120 DENV isolates was done from laboratories of tertiary care hospitals of Punjab for analysis of sequencing of the whole genome. Only 23 samples were sequenced after viral isolation, quantification and cDNA synthesis. A total of 133 different types of mutations were detected along the entire length of NS.1. The most common mutations with the highest frequency were, K324R and K347R (n=7), D278N (n=6), K174R, and F178S (n=4), found at c-terminal of NS.1 protein. Mutations K347R, K174R, and F178S are novel. Future DENV vaccination development research will be especially profited by the mutations found in the current study. During each DENV outbreak in different places, studying genomic variations is crucial for strengthening societal health and developing new policies for future outbreaks.